The Relocation Phenomenon of Bonded Zone Industries to Central Java: Casual Factors in View of Investment and Impact on Labor Absorption - Kristiawan, Bambang; Rosyadi, Slamet; Tobirin, T. (Golden Ratio of Social Science and Education, 2025)
This study examines the relocation of labor-intensive industries from the Jabotabek region to Central Java, focusing on bonded zone facilities in the ex-Residency of Pekalongan, including Brebes Regency. Using a qualitative research design, data were collected through in-depth interviews with company managers and customs officials, supported by regulatory documents and statistical records. Findings indicate the main drivers of this industrial shift are cost advantages, particularly lower regional minimum wages (UMR). In Jabotabek, wages average around IDR 4.5 million monthly, while in Central Java, they remain around IDR 2–2.5 million, with Brebes at IDR 2.018 million (2023). For factories employing over 9,000 workers, this gap leads to potential savings of more than IDR 270 billion annually. Additional factors include cheaper land prices for factory sites and improved infrastructure, especially the Trans-Java toll road, which facilitates logistics and access to ports. Economically, 36 bonded-zone companies in the region employ 67,559 workers, with 41,268 in Brebes alone. However, this represents only about 3% of Brebes’s productive-age population, showing that industrialization alone may not resolve unemployment fully. Poverty rates have declined slowly from 17.43% in 2021 to 15.78% in 2023, highlighting a limited immediate impact. Although industrial expansion stimulates local economies by supporting informal sectors like food services, housing, and transportation, there are concerns about fostering a narrow “labor mentality” that limits entrepreneurship and shifts youth away from agriculture. The study concludes that while industrial relocation offers economic opportunities, a balanced policy is needed to ensure sustainable development, improve local welfare, and support economic diversification in Central Java.